Briquetes a partir de resíduos de biomassa agrícola - Costa, Susana Claudete (2019)
Biomass such as rice husk, citrus peel and coffee grounds are among the most abundant sources for converting crops into biofuel briquettes. It is important to note that sustainable bioenergy must be highly efficient; therefore, the lower and upper calorific power of the briquettes produced from rice, orange, mandarin, lemon, coffee grounds (espresso or past) using corn starch or potato peel as binders were evaluated. For a group of specimens, glycerol, citric acid and acetic acid were included in the preparation of solid biofuels. In addition to the lower and upper calorific power of the specimens, the total moisture, ash and silica content was determined. It was also determined the compressive strength, in which all the samples had a suitable maximum resistance for briquettes of domestic use, and some compositions reached the resistance of briquettes for industrial use. For biofuel briquettes with coffee grounds the best results of mechanical strength, lower and upper calorific power were found for the specimens with past coffee. For the briquettes with citrus peels and rice husks, it is emphasized that greater mechanical resistance was obtained with the addition of citric acid, acetic acid and glycerol. Replacing the rice husks with tangerine peels resulted in a reduction in silica mass. In addition, the nutrients (N, P, K, Ca and Mg) and heavy metals (Cu, Zn, Fe, Mn, Cd, Pb, Cr and Al) were quantified in the ash of specimens with bark of mandarin; these can be considered for addition to the soil as the amount of nutrients increases proportionally to the amount of mandarin peels in the biofuel. Biofuel briquettes with higher amount of mandarin peels presented higher values for upper and lower heating values (UHV and LHV), lower calorific power, which were 19.18 MJ / kg and 17.92 MJ / kg. All the specimens developed were able to replace traditional sources of heat, such as firewood (7.12 to 10.47 MJ / kg), with better energy performance.